Effects of JPEG 2000 compression on automated DSM extraction: Evidence from aerial photographs - Shih, TY; Liu, JK (My University, 2005)
This paper evaluates the effects of JPEG 2000 compression on automated digital surface model (DSM) extraction, using the area-based matching technique. Two stereopairs of aerial photographs, which have different photo scale, pixel size, and topographic type, are used as the images for the experiments. In the experiments, the DSM generated from the uncompressed image is set as the reference, and the elevation accuracy is computed for a range of compression ratios (2:1 to 100:1). The results show that the employed indices of image quality based on the JPEG 2000 compression are clearly superior to the commonly used JPEG compression technique-especially for high compression ratios. However, the elevation accuracy varies with the compression ratios. Also, JPEG 2000 compression does not have a significant influence on the percentage of the successful matching rate. In addition, a near linear fall-off is observed in extracted DSM accuracy with increasing compression ratios.
Keywords: area-based matching; digital surface model; image compression; JPEG 2000